Destructive Impacts of Corruption Processes on the Formation of Future Generations' Mentality - Eugene Vdovychenko (International Society of Philosophy and Cosmology, 2016)
The paper looks at the dangerous aspects of corruption impacts on the formation of future generations' mentality. It is wellknown that higher education institutions are the organizations that are not only foremost in research work in all the activities, but they also train the country' future elite. Corruption in these institutions has a negative impact on the value, volume and quality of education services, reducing the level of the society's trust, influencing the results of studies and their potential ef ect on the longterm social and economic development. It is necessary to highlight that this social disease is especially dangerous for the younger generation. The young often feel that corruption influences them since their adolescence and learn from this negative experience, then they bring it into their adult life, and this creates a vicious circle of problems. Therefore, nowadays it is necessary to resist the negative impact and socioeconomic consequences of corruption concerning students. Not only is the professional training of young people getting worse, but also their way of thinking, moral precepts and attitude towards the world. It can cause total moral and spiritual degradation of the society in future.